CLUSTER STRUCTURE OF MELTS - N. K. Tolochko; A. A. Andrushevich (Литьë и металлургия)
Brief analysis of contemporary conceptions of metal melt cluster structure is presented and probable mechanisms of melt crystallization and ingot melting processes are considered on the base of these conceptions.